Hydatidiform mole clinical and pathological characteristics - Pacheco D., José (2002)
Objective: To determine clinical and pathological findings in hydatidiform mole. Design: Descriptive retrospective study. Material and methods: All cases de molar pregnancy attended at Dos de Mayo National Hospital (HNDM) between 1998 and 2001 were reviewed. Results: Twenty-four cases of hydatidiform mole were attended; mean age was 26,4 years ± 6,4 and gestational age 13,1 weeks ± 3,3. Past history only showed 1 and 3 cases of hyperemesis gravidarum and previous abortions, respectively; 18 pregnant women were multiparae. Symptoms on admission were hypogastric pain (75%), nausea and vomiting (29,2%), dysuria (20,8%) and headache (8,3%); and clinical sigsn, fetal absence (100%), vaginal bleeding (91,7%), soft uterus (45,8%), discordant uterine height (33,3%) and expulsion of vesicles (25%). Ultrasound diagnosis was hydatidiform mole with fetal absence (100%), ovarian enlargement (29,2%) and tecaluteinic cysts (25%). Average βhCG was 18167 UI/L. Transvaginal misoprostol was used previouly to dilatation and curettage in 37,5%. Pathology findings were corionic epitheliu moderate hyperplasia (62,5%), avascular estroma (50%) and edematous villi (20%). Conclusion: Our findings denote infrequent characteristics to the literature description on this pathology.